Gamification in the classroom: Kahoot! As a tool for university teaching innovation - Aibar-Almazán, Agustín; Castellote-Caballero, Yolanda; Carcelén-Fraile, María del Carmen; Rivas-Campo, Yulieth; González-Martín, Ana María (Frontiers in Psychology, 2024)
Objectives The purpose of this study has been to evaluate the use of gamification in the classroom, in terms of its effects on attention, concentration, creativity, and generic capabilities, for university students enrolled in a Bachelor’s degree program in Physiotherapy. Methods An experimental design was implemented, using three groups differentiated by their time of exposure to the game (0 min, 30 min, or 60 min per week). The sample consisted of 73 s-year students from a Bachelor’s degree program in Physiotherapy. The theoretical content for each class was taught during a period of 4 months, reinforced by use of the Kahoot! Online platform. Selective attention and concentration were evaluated using the d2 Test of Attention; creative intelligence using the Creative Intelligence Test (CREA); and generic capabilities using the capabilities subscale of the Student Engagement Questionnaire (SEQ). Results The study’s participants had a mean age of 19.51 ± 0.9 years, and it has demonstrated that use of Kahoot! For longer periods of time, i.e., more than 60 min per day, can improve essential skills in university students, such as attention, creativity, critical thinking, self-managed learning, adaptability, problem solving, and computer literacy. This study’s results show that integrating Kahoot! Into the educational environment, especially with longer sessions that allow for deeper immersion in the game, produces benefits by stimulating various cognitive aspects and enhancing complex skills. Conclusion This study has demonstrated that use of Kahoot! Improves key skills such as attention, creativity, and critical thinking, especially when longer sessions are used. It is also suggested that its use should be balanced with other educational activities, in order to achieve comprehensive development for the students.